2014
DOI: 10.1039/c4sm02347a
|View full text |Cite
|
Sign up to set email alerts
|

Anionic deep cavitands enable the adhesion of unmodified proteins at a membrane bilayer

Abstract: An anionic self-folding deep cavitand is capable of immobilizing unmodified proteins and enzymes at a supported lipid bilayer interface, providing a simple, soft bioreactive surface that allows enzymatic function under mild conditions. The adhesion is based on complementary charge interactions, and the hosts are capable of binding enzymes such as trypsin at the bilayer interface: the catalytic activity is retained upon adhesion, allowing selective reactions to be performed at the membrane surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…We have also previously shown that host 1 can bind proteins at membrane bilayer interfaces via charge-based interactions. 28 As the neutral cavitand 2 is the host that is most capable of non-KMe 3 recognition, however, it is most likely that hydrophobic association is the dominant factor here.…”
Section: Resultsmentioning
confidence: 95%
“…We have also previously shown that host 1 can bind proteins at membrane bilayer interfaces via charge-based interactions. 28 As the neutral cavitand 2 is the host that is most capable of non-KMe 3 recognition, however, it is most likely that hydrophobic association is the dominant factor here.…”
Section: Resultsmentioning
confidence: 95%
“…While determining the exact concentration of cavitand 1 absorbed in the membrane is challenging, studies with vesicles preloaded with cavitand suggest that a 2% cavitand loading gives a similar amount of guest recognition. 27 The dissociation constant of R-NMe 3 + -based guests for cavitand 1 in a POPC bilayer is on the order of micromolar, 26 indicating that the host is most likely saturated with initiator before ATRP. Finally, the living nature of the polymerization was tested.…”
Section: Resultsmentioning
confidence: 99%
“…31 In a bilayer environment, the effect is magnified, enhancing salt bridge interactions between anionic 1 and cationic macromolecules such as trypsin. 27 We attribute this difference to the deformation of the bilayer upon cavitand incorporation providing a small hydrophobic “pocket” above the cavitand rim, although the exact cause of the enhanced interactions is not completely clear. This effect is specific to proteins with high isoelectric points (pI) such as trypsin or cytochrome c .…”
Section: Introductionmentioning
confidence: 95%
“…1b and c). 26,27 It has an open-ended, defined cavity that is capable of selective recognition of substituted trimethylammonium (R-NMe 3 + ) salts such as acetylcholine, driven by favorable shape-filling interactions between host and guest, as well as via cation–π interactions between the softcation and the electron rich aromatic walls of the cavity. 30 The open-ended nature of 1 allows the substrates to protrude into the exterior milieu, thus allowing variation in target, and different proteins and small molecules 25 can be immobilized via the use of the R-NMe 3 + binding “anchor” (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation